By substitution method, we can solve the system of equations:
From the second equation, we can express x in terms of y:
y = x + 1
x = y - 1
Now we substitute this value of x in the first equation:
y = -x - 3
y = -(y - 1) - 3
y = -y + 1 - 3
y = -y - 2
To simplify the equation, we add y to both sides:
2y = -2
y = -1
Substituting this value of y back into the second equation:
x = y - 1
x = -1 - 1
x = -2
Therefore, the solution to the system of equations is the ordered pair (-2, -1).
y=-x - 3
y=x+1
the solution to the system is (type and ordered pair)
1 answer